2018
DOI: 10.1038/s41418-018-0090-y
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering and deciphering the pro-invasive role of HACE1 in melanoma cells

Abstract: HACE1 is an E3 ubiquitin ligase described as a tumour suppressor because HACE1-knockout mice develop multi-organ, late-onset cancers and because HACE1 expression is lost in several neoplasms, such as Wilms' tumours and colorectal cancer. However, a search of public databases indicated that HACE1 expression is maintained in melanomas. We demonstrated that HACE1 promoted melanoma cell migration and adhesion in vitro and was required for mouse lung colonisation by melanoma cells in vivo. Transcriptomic analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…The results of the present study indicated that demethylation of the HACE1 promoter enhanced its expression, and inhibited proliferation and colony formation of liver cancer cells. However, a previous study demonstrated that HACE1 promotes melanoma cell migration and adhesion in vitro and that it is required for mouse lung colonization by melanoma cells in vivo (24). These findings indicated that whether HACE1 acts as a tumour suppressor gene or oncogene may depend on the cancer type.…”
Section: Discussionmentioning
confidence: 97%
“…The results of the present study indicated that demethylation of the HACE1 promoter enhanced its expression, and inhibited proliferation and colony formation of liver cancer cells. However, a previous study demonstrated that HACE1 promotes melanoma cell migration and adhesion in vitro and that it is required for mouse lung colonization by melanoma cells in vivo (24). These findings indicated that whether HACE1 acts as a tumour suppressor gene or oncogene may depend on the cancer type.…”
Section: Discussionmentioning
confidence: 97%
“…E-cadherin is a biomarker for cancer [ 18 , 40 ] and is attenuated and reduced in many cancers [ 41 43 ], especially in lung and breast cancers. E-cadherin loss in tumor cells leads to decreased adhesion between tumor cells, which favors epithelial-mesenchymal transition [ 44 ] and promotes the ability of tumor cells to invade and metastasize. In metastatic lung cancer (stages III and IV), E-cadherin protein levels were significantly lower than those in nonmetastatic stages (I and II).…”
Section: Discussionmentioning
confidence: 99%
“…Even though HACE1 behaves as an anti-oncogene in most reports, its function in melanoma may be cell-specific tumorigenesis. HACE1 plays a pro-oncogenic role in melanoma by regulating fibronectin (FN) secretion and K27 ubiquitination of FN [24].…”
Section: Hace1mentioning
confidence: 99%